Higher versus lower mean arterial blood pressure after cardiac arrest and resuscitation (MAP-CARE): A protocol for a randomized clinical trial - Niemelä, V H; Reinikainen, M; Nielsen, N; Bass, F; Young, P; Lilja, G; Dankiewicz, J; Hammond, N; Hästbacka, J; Levin, H; Moseby-Knappe, M; Saxena, M; et al. (Acta anaesthesiologica Scandinavica, 2025)
BACKGROUND: In patients resuscitated after cardiac arrest, a higher mean arterial pressure (MAP) may increase cerebral perfusion and attenuate hypoxic brain injury. Here we present the protocol of the mean arterial pressure after cardiac arrest and resuscitation (MAP-CARE) trial aiming to investigate the influence of MAP targets on patient outcomes. METHODS: MAP-CARE is one component of the Sedation, Temperature and Pressure after Cardiac Arrest and Resuscitation (STEPCARE) 2 x 2 x 2 factorial randomized trial. The MAP-CARE trial is an international, multicenter, parallel-group, investigator-initiated, superiority trial designed to test the hypothesis that targeting a higher (>85 mmHg) (intervention) versus a lower (>65 mmHg) (comparator) MAP after resuscitation from cardiac arrest reduces 6-month mortality (primary outcome). Trial participants are adults with sustained return of spontaneous circulation who are comatose following resuscitation from out-of-hospital cardiac arrest. The two other components of the STEPCARE trial evaluate sedation and temperature control strategies. Apart from the STEPCARE trial interventions, all other aspects of general intensive care will be according to the local practices of the participating site. Neurological prognostication will be performed according to European Resuscitation Council and European Society of Intensive Care Medicine guidelines by a physician blinded to allocation group. The sample size of 3500 participants provides 90% power with an alpha of 0.05 to detect a 5.6 absolute risk reduction in 6-month mortality, assuming a mortality of 60% in the control group. Secondary outcomes will be poor functional outcome 6 months after randomization, patient-reported overall health 6 months after randomization, and the proportion of participants with predefined severe adverse events. CONCLUSION: The MAP-CARE trial will investigate if targeting a higher MAP compared to a lower MAP during intensive care of adults who are comatose following resuscitation from out-of-hospital cardiac arrest reduces 6-month mortality.
Keywords: výsledek terapie; kardiopulmonální resuscitace; Out-of-Hospital Cardiac Arrest; zástava srdce mimo nemocnici; multicentrické studie jako téma; srdeční zástava; Resuscitation; cardiac arrest; Coma; target; randomizované kontrolované studie jako téma; Adult; dospělí; randomized clinical trial; blood pressure; Heart Arrest; Arterial Pressure; Treatment Outcome; arteriální tlak; lidé; Cardiopulmonary Resuscitation; ženské pohlaví; Humans; Randomized Controlled Trials as Topic; kóma; Multicenter Studies as Topic; hodnocení ekvivalence jako téma; resuscitace; Female; Equivalence Trials as Topic